2017
DOI: 10.1139/cgj-2015-0290
|View full text |Cite
|
Sign up to set email alerts
|

A new simplified method and its verification for calculation of consolidation settlement of a clayey soil with creep

Abstract: The calculation of the consolidation settlement of clayey soils with creep behaviour has been a challenging issue with a long history. After a brief review the assumptions made in the two methods based on Hypothesis A and Hypothesis B, the authors present a new simplified hypothesis B method for calculation of consolidation settlement of a clayey soil with creep. Equations of this method are derived based on the “equivalent time” concept for different stress–strain states. This simplified Hypothesis B method i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
57
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 24 publications
3
57
0
Order By: Relevance
“…when n = 1. In previous study, Yin and Feng suggested α 0.8 for a single soil layer. In the study of this paper, the authors have found that α is related to OCR and can be taken as α = 0.4 + 0.2OCR.…”
Section: A New Simplified Hypothesis B Methods For Calculating Consolimentioning
confidence: 94%
See 3 more Smart Citations
“…when n = 1. In previous study, Yin and Feng suggested α 0.8 for a single soil layer. In the study of this paper, the authors have found that α is related to OCR and can be taken as α = 0.4 + 0.2OCR.…”
Section: A New Simplified Hypothesis B Methods For Calculating Consolimentioning
confidence: 94%
“…Based on Hypothesis B and ‘equivalent time’ concept , Yin , Yin and Feng proposed a new simplified Hypothesis B method for 1‐D consolidation settlement prediction for one single layer of a clayey soil as follows: leftSitalictotalB=S"primary"+Sitaliccreep=UvSf+αScreep,f+1αS"secondary"fort1dayttEOP,fieldforS"secondary" where S " primary " = U v S f denotes the settlement of ‘primary’ consolidation at any time t . U v is the average degree of consolidation for the soil layer, and S f represents the final settlement at the end of ‘primary’ consolidation.…”
Section: Brief Review Of the New Simplified Methods Based On Hypothesimentioning
confidence: 99%
See 2 more Smart Citations
“…Borja and Choo considered the macro‐ and micro‐scales and simulated the “secondary compression” during 1‐D consolidation. Yin and Feng and Feng and Yin proposed a simplified Hypothesis B method to calculate the consolidation settlement for both single and double soil layers exhibiting creep. Wang, Sun, Li, and Ye provided a semi‐analytical solution to Terzaghi's 1‐D consolidation of a viscoelastic soil fractional derivative Kelvin‐Voigt model.…”
Section: Introductionmentioning
confidence: 99%